Dependence of electron states density of intercalated layer crystal on the intercalant concentration - Tovstyuk, N.K.; Lukiyanets, B.A. (Condensed Matter Physics, 2002)
Electron states density ρ(ω) depending on the intercalant atoms concentration
within the framework of a virtual crystal is investigated. An essential
change of ρ(ω) in the vicinity of the band bottom of the initial layer crystal
at certain energy parameters of a crystal matrix, intercalant and their
mutual mixing is obtained. Such a change can manifest itself specifically in
optical properties in the region of fundamental absorption В рамках моделі віртуального кристала досліджена залежність густини електронних станів р(ω) від концентрації інтеркалянта. Суттєві зміни р(ω) в околі дна зони вихідного шаруватого кристала отримано в залежності від енергетичних параметрів гратки і інтеркалянта та їх взаємного перемішування. Такі зміни можуть проявлятися, зокрема, в оптичних властивостях в області власного поглинання.